Peran Pendidikan Karakter dalam Membentuk Kemampuan Berfikir Kritis Generasi Muda Indonesia - Al Asadullah, Salahuddin; Nurhalin, Nurhalin (Kaisa: Jurnal Pendidikan dan Pembelajaran, 2021)
This article aims to determine the role of character education in building the critical thinking skills of the young generation in Indonesia. The method used is literature review or literature study, which contains theories that are relevant to research problems. Based on the discussion, there are roles for character education in building critical thinking skills for the younger generation, including the Strengthening Character Education program. Also, learning activities within the framework of student character development can use a contextual approach as a learning and teaching concept that helps teachers and students relate the material being taught to real-world situations. To support this system, the younger generation also needs to familiarize themselves with dialogue, communication, discussion, and attending various scientific seminars. By engaging in activities based on academic intellectuals, they can practice thinking in a structured, logical and systematic manner, broad insight, inclusive, rational, critical, selective, and constructive in observing themself and social reality. By implementing character values, the role of the younger generation in Indonesia is increasingly real and can bring change for the better.Tujuan dari artikel ini adalah untuk mengetahui peran pendidikan karakter dalam membentuk kemampuan berpikir kritis generasi muda di Indonesia. Metode yang digunakan adalah studi perpustakaan atau studi literatur, yang berisi teori yang relevan dengan masalah penelitian. Selain itu, kegiatan pembelajaran dalam kerangka pengembangan karakter siswa dapat menggunakan pendekatan kontekstual sebagai konsep belajar mengajar untuk membantu guru dan siswa dalam menghubungkan materi yang diajarkan dengan kehidupan sehari-hari. Untuk mendukung sistem ini generasi muda juga perlu melibatkan diri untuk berdialog, berkomunikasi, diskusi, dan mengikuti berbagai seminar ilmiah. Dengan melibatkan diri ke dalam kegiatan berbasis intelektual akademik, mereka dapat berlatih berpikir terstruktur, logis dan sistematis, berpikiran luas, berwawasan luas, inklusif, rasional, kritis, selektif, dan konstruktif dalam melihat realitas diri dan sosial. Dengan mengimpelentasikan nilai-nilai karakter, peran generasi muda di Indonesia semakin nyata dan dapat membawa perubahan, tentu kearah yang lebih baik.